Development of Pop-up Storybooks Media Building Space to Improve Students’ Understanding of Geometry Concepts in Grade VI Elementary School - Nurul Fatimah; Dani Kusuma (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the process of developing pop-up storybook learning media for spatial figures to improve the understanding of geometry concepts for grade VI elementary school students, to determine the validity of pop-up storybook learning media for spatial figures, to determine the practicality of pop-up storybook learning media for spatial figures, and to determine the effectiveness of pop-up storybook learning media for spatial figures. The research is a Research and Development (RD) type with the ADDIE development model, and the research subjects include grade VI students at Mlilir 02 Elementary School located in RT 02 RW 04 Mlilir Village, Bandungan District, Semarang Regency. The data collection techniques employed in this study included observation, tests, interviews, and questionnaires, which were subsequently analyzed using effectiveness tests and practicality tests. Based on the results of the study, it was found that the results of the N-Gain value test in the table above, it is known that the N-Gain score has an average value (mean) of 0.6020. Thus, it can be concluded that the use of Pop-up Storybook media for spatial structures in improving students' understanding of geometric concepts is quite effective for use in learning.